Description of Erythrocytes of Striped Catfish (Pangasionodon hypophthalmus) Infected by Edwardsiella tarda Treated with Mango Leaf (Mangifera indica) - Tungkup, Mariana Lumban; Syawal, Henni; Riauwaty, Morina (Faculty of Fisheries and Marine, Universitas Riau, 2021)
This research has been carried out from November to December 2019 at the Laboratory of Parasites and Fish Diseases at the Fisheries and Marine Faculty of Riau University. The aim of the study was to obtain the best dose of mango leaf solution for the treatment of striped catfish (P. hypophthalmus) infected with E. tarda, seen from the erythrocyte picture. The method used was an experiment with a Completely Randomized Design (CRD) of a factor of five treatment levels and replications three times. Test fish used were striped catfish measuring 8-12 cm, with a total of 150 fish. The treatments used for treatment were 1000 ppm, 1200 ppm, 1400 ppm, negative controls (not infected and not treated), and positive controls (infected and not treated). Parameters measured and observed among others; total erythrocytes, hemoglobin levels, hematocrit values, erythrocyte cell morphology and survival rate. The results showed that apple mango leaf solution (M. indica) was able to treat conjoined striped catfish infected with E. tarda by Emmersion method. The best treatment of 1200 ppm is characterized by an average total erythrocyte, mean total erythrocytes 149.33 x 104 cells / mm3, hemoglobin level 9.03 g / dL, hematocrit value 35.67% and the survival of the test fish after treatment is 86.67%. The results of water quality measurements during the study, namely temperature 27.00-27.46 0C, pH 6.1-6.77, dissolved oxygen 3.53-3.87 mg/L, and ammonia 0.02 mg/L.